Efficient Immobilization of a Cadmium Chemosensor in a Thin Film: Generation of a Cadmium Sensor Prototype - Bronson, R. Todd (2005)
The development of an ion-selective chemosensor for Cd2+ allows generation of a “real-time” sensor. Immobilization of the chemosensor on quartz was achieved in a simple monolayer and in a thin film using a polymer intermediary. As intended, the thin film contains much more chemosensor than the monolayer and provides measurable responses to aqueous Cd2+ concentrations below 1 μM. Alkali and alkaline earth ions do not interfere with Cd2+ sensing; Zn2+ and Cu2+ are potential interferents.